2005
DOI: 10.1111/j.1464-410x.2005.05411.x
|View full text |Cite
|
Sign up to set email alerts
|

A stereological analysis of fibrosis and inflammatory reaction induced by four different synthetic slings

Abstract: OBJECTIVES To analyse quantitatively, using stereological methods, the density of the collagen fibres induced by four types of sling materials, and verify by a histopathological analysis the corresponding inflammatory reaction, as fibrosis secondary to sling implantation is considered responsible for restoring urethral support and re‐establishing continence in women with stress urinary incontinence, and new synthetic materials that promote adequate fibrosis with the least intensity and duration have been propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
(20 reference statements)
0
24
0
1
Order By: Relevance
“…The amount and type of collagen production stimulated by different materials may vary owing to their respective properties and environment [10,11]. Using an animal model, de Almeida et al noted that at day 60, both Prolene® (1,500-μm pores) and Marlex® (PP, 600-μm pores) induced a similar inflammatory response.…”
Section: Quality Of Scar Formationmentioning
confidence: 98%
“…The amount and type of collagen production stimulated by different materials may vary owing to their respective properties and environment [10,11]. Using an animal model, de Almeida et al noted that at day 60, both Prolene® (1,500-μm pores) and Marlex® (PP, 600-μm pores) induced a similar inflammatory response.…”
Section: Quality Of Scar Formationmentioning
confidence: 98%
“…The picro-sirius stain was chosen because of its fine results in collagen staining in previous studies using similar methods [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…[45] Histopathological analyses by Wiedemann and Otto [53] indicated that growth factors contained in the small intestinal submucosa (SIS) most likely result in the significant reduction in donorrecipient immunogenic reaction and scar tissue formation seen with this type of PVS. Thiel et al [54] analyzed the fibrotic and inflammatory reaction caused by four different sling materials in 70 Wistar rats. The authors found that the amount of inflammation and collagen fibers was higher in SIS compared to polycaprolactone, polylactic acid copolymers, and monofilament polypropylene mesh.…”
Section: ) Pubovaginal Sling Xenograft Materialsmentioning
confidence: 99%